A component analysis of behavioral skills training with volunteers teaching motor skills to individuals with developmental disabilities. (13th August 2019) - Davis, Sarah; Thomson, Kendra; Connolly, Maureen
Abstract : This study included a component analysis of behavioral skills training (BST) for teaching volunteers how to use this training method to support individuals with developmental disabilities in a physical education program. In an alternating treatment design embedded within a multiple baseline design across five participants, the number of BST steps that volunteers completed correctly while teaching four motor skills was measured. In the initial training phase, each motor skill was taught to volunteers using a specific component of BST (i.e., instructions, modeling, rehearsal, or feedback). In subsequent training phases, BST components were combined to teach the volunteers the motor skills for which they did not reach a predetermined mastery criterion (a score of four correct responses across two consecutive trials). Maintenance was assessed. Results indicated that individual components of BST alone were sufficient for volunteers to meet the mastery criterion; however, the full BST framework was necessary for skill maintenance. Strengths, limitations, and recommendations for future research are discussed.